Two new onyсhiurid species (Collembola, Onychiurinae) inhabiting morel fruit bodies in southwest China - Liu, Jie; Gao, Meixiang; Xie, Zhijing; Sun, Xin (Zootaxa, 2019)
Two new species Oligaphorura shifangensis sp. nov. and Onychiurus qingchuanensis sp. nov. living on mushrooms (morels) were reported from southwest China. Oligaphorura shifangensis sp. nov. is similar to known species O. schoetti (Lie-Pettersen, 1896), O. groenlandicus (Tullberg, 1876) and O. sibirica (Weiner & Kaprus’, 2014) as having the same pso formulae (32/133/33343 dorsally and 11/000/00000 ventrally), five papillae in AIIIO, subcoxae 1 of legs I–III with 1 pso each, 11 chaetae in the distal whorl of tibiotarsi, ms present on Th. II and III terga and the presence of anal spines; but they can easily be separated by the labial palp type, ventral psx formula, ratio of unguiculus/unguis and the presence/absence of cuticular fold in furcal remnant. Onychiurus qingchuanensis sp. nov. shares the number of dorsal pso with only three congeners, namely O. bhattii, O. fraterculi and O. steinmanni. They can easily be distinguished by the number of ventral and subcoxal pso, ventral psx and papillae on AIIIO.